Case Report: The ultrasound features of acquired cystic disease-associated renal cell carcinoma: a case series - Yang, Yanrong; Chen, Hongyan; Li, Yongzhong; Zhou, Jiaojiao (Frontiers in Oncology, 2023)
Background: Acquired cystic disease associated renal cell carcinoma (ACD-RCC) is a new subtype listed by the 2016 World Health Organization (WHO) classification, which occurred in end-stage renal disease (ESRD) patients. The main diagnosis form of ACD-RCC is pathological biopsy and immunohistochemistry. Studies about the ultrasound features of ACD-RCC were rare. This study will introduce the imaging features of four cases diagnosed as ACD-RCC. Case presentation: We searched all the inpatients from January 2016 to May 2022 with the diagnosis of ACD-RCC in the Pathology database. Pathology, ultrasound, and radiology readings are performed by experienced physicians with the title of attending physician or higher. Four cases were included in this study, all of whom were males, aged from 17 to 59. Two cases suffered from ACD-RCC in both kidney and kidney nephrectomies were performed. One case underwent renal transplantation, whose creatinine was back to normal, and the rest were on hemodialysis, whose creatines were still high. In the pathological images, heteromorphic cells and oxalate crystals can be seen. Both ultrasonography and enhanced CT show enhancement of the solid component of the occupancy. We follow up through outpatient and telephone visits. Conclusion: In clinical work, ACD-RCC should be considered when mass presents under the background of multiple cysts in the kidney in ESRD patients. A timely diagnosis will be helpful to the treatment and the prognosis.